Inorganic PM and K emissions during ashing of solid biofuels and Kaolinite – Data measurement in laboratory scale. (15th July 2021) - Höfer, Isabel; Gollmer, Christian; Kaltschmitt, Martin
Highlights: Introduction of a new laboratory scale sampling method for inorganic PM during the ashing process of different biomasses. Measuring the inorganic PM and K emissions during ashing of various biomasses. Analysis the influence of the additive Kaolinite on the inorganic PM and the K content in the PM in the laboratory scale. Analysis of the elemental composition in the 1, 200 °C ash and the resulting reactions and release mechanisms. Abstract: During combustion of solid biofuels, a broad variety of particulate matter (PM) is released into the atmosphere. Combustion systems are constantly being further improved according to the 3‑T rule (time, temperature and turbulence), thus further reducing the proportion of organic compounds in the PM. The inorganic share in PM is affected by this optimization in a rather small amount and therefore gains relevance. Woody and herbaceous biofuels are characterized by a varying elemental composition responsible for a different ash chemistry and thus for various amounts of emitted particles. To estimate the potential PM emissions as well as the corresponding K content related to the respective elements in the solid biofuels during combustion a new inorganic PM sampling method in the laboratory scale has been developed and tested. This method can forecast the amount of released inorganic PM and K during ashing of different biomasses. Here the inorganic PM of five different biomasses (i.e., spruce wood, wheat straw, spruce bark, corn cob and miscanthus) is measured. In addition, the influence of the additive Kaolinite (1 mas-%) is tested regarding the inorganic PM and K emissions during ashing of the biomasses spruce wood and miscanthus. Based on the obtained results from the ash analyses, conclusions concerning the applicability of the presented inorganic PM sampling method are derived. It can be shown, that the addition of 1 mas-% Kaolinite reduces the amount of K in the inorganic PM in the spruce wood and miscanthus sample by 55% and by 78%, respectively.